Cloud computing: analysing the trade-off between user comfort and autonomy - Primavera De Filippi (Internet Policy Review, 2013)
This article presents a general analysis of how user autonomy in cloud computing is increasingly put into jeopardy by the growing comfort and efficiency of the user-interface. Although this has not been, thus far, explicitly addressed by law, it is a fundamental ethical question that should be carefully assessed to guide the future deployment of cloud services. Different policy decisions might, in fact, significantly affect user's fundamental rights and online freedoms by shifting the balance from one part of the trade-off to the other. This article aims to explore emerging trends in cloud computing technologies and analyse them from an ethical perspective. among other in order to identify the issues they might raise, and the extent to which current laws and regulations take these issues into account.
Keywords: 300; Cloud services; Autonomy; Comfort; Proprietary software; Interoperability; End-to-end; Walled garden; User lock-in; Profiling